Pengaruh Edukasi Gizi Terhadap Pengetahuan Dan Self Management Pada Penderita Diabetes Melitus Tipe 2 (Al GIZZAI: PUBLIC HEALTH NUTRITION JOURNAL, 2023)
According to the International Diabetes Federation (IDF) in 2019 there were 463 million people suffering from diabetes. The purpose of this study was to determine the effect of nutrition education on the level of knowledge and self management in patients with type 2 diabetes mellitus at the Somba Opu Health Center in 2020. The type of research used is quantitative with pre post one group design research, and a quasy experiment approach. Accidental sampling technique with a total sample of 45 people with type 2 diabetes mellitus. Data collection used questionnaires, video media and leaflets. Data analysis used consists of 2 stages, namely univariate and bivariate (Anova test and Friedman test). The results of this study indicate that there is no effect of nutrition education on the level of pre-test knowledge in each intervention group, namely the p value ꞊ 0.155 patients with type 2 diabetes mellitus. There is an effect of nutrition education on the level of knowledge post test p value = 0.001, the level of self management pre test p value = 0.001 and the level of self management post test p value = 0.000 in each intervention group in patients with type 2 diabetes mellitus. With the incidence of diabetes mellitus, it is hoped that health workers will further improve the program in the field of counseling and provide education related to dietary therapy for food selection